Applied Study Of The Processability Theory OF Arabic Learners In The Islamic University Of Madinah/ دراسة تطبيقية لنظرية قابلية المعالجة على مجموعة من متعلمي اللغة العربية في الجامعة الإسلامية بالمدينة المنورة - Alhazmi, Muhammad Zafer (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This paper focuses on an essential aspect of teaching Arabic to non-native speakers, drawing on applied linguistics, a field that seeks to deepen our understanding of second language acquisition. Many theories exist in this field, but their validity can only be tested through practical application. This study applies the Processability Theory to assess Arabic language learners' proficiency. The study sample includes twenty international students from the Islamic University of Medina: students of the College of Sharia (first year) and the College of Arabic Language (eighth year). The main goal is to highlight the relevance of Processability Theory in evaluating learners' levels. The study also provides statistical analysis regarding the student's progress in learning Arabic. According to Processability Theory, language learning progresses through five levels. The application in this study focuses on three of these levels: (1) the third level, represented by the correct use of the definite article (Al-); (2) the fourth level, focused on sentence structures with basic (VSO) and free word order (SVO); and (3) the fifth level, dealing with complex sentences. The findings reveal a significant difference between the groups regarding correctly using the definite article. First-year students made considerably more errors compared to eighth-year students. However, the gap between the two groups narrowed at the fourth and fifth levels. Their use of sentences under the fourth level was similar, and while their use of complex sentences (fifth level) was rare, it did not yield statistically significant results. Nonetheless, eighth-year students showed a slight numerical advantage in this area. Overall, this study demonstrates the importance of Processability Theory in assessing learners' proficiency and highlights the variation in language learning progression.